The model of growth of enterprise income with an increase in output while reducing prices - Kalitine, Boris S.; Sheleg, Evgeny A. (Journal of the Belarusian State University. Economics, 2021)
The work examines the potential of the enterprise when using the economic policy of the increasing output and decreasing prices (IODP), namely the increase in output with a simultaneous decrease in its price on the commodity market. The results were obtained on the basis of constructing a certain mathematical model that allows expressing the manufacturer’s net proceeds in terms of essential market parameters. This includes: the price and volume of sales of goods or services provided, the absolute value of the coefficient of price elasticity of demand, the inflation rate for the period under consideration, the coefficient of production costs. The strengths and weaknesses of economic actions in the conditions of the IODP are revealed. A nonlinear programming problem is formulated to find the best way to implement the IODP method. The search for a solution to this problem and its economic interpretation was tested on numerical data.